Dedolarisasi di Indonesia: Tantangan dan Peluang Penguatan Ekonomi Syariah - Muh. Ridla Syafiun Makhsush; Ulyan Nasri; Muhammad Salahuddin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study examines the issue of dedollarization in Indonesia, focusing on the challenges and opportunities for strengthening the Islamic economy. Dedollarization, defined as reducing dependency on the US dollar in economic and financial transactions, is a crucial strategy for enhancing national economic independence. In the context of the Islamic economy, dedollarization presents opportunities to reinforce a financial system based on Islamic values, which emphasize justice, transparency, and sustainability. This research employs a qualitative approach using literature review and policy analysis methods. The findings indicate that the main challenges of dedollarization in Indonesia include dependence on dollar-based international trade, domestic currency stability, and the limited financial infrastructure to support this transition. However, significant opportunities are also evident, such as the vast potential of the Islamic economy market, supportive government regulations, and increasing public awareness of the importance of an economic system rooted in Islamic principles. The implications of dedollarization for the Islamic economy include enhancing the competitiveness of Islamic financial institutions, expanding the use of local currency in international transactions, and strengthening the halal ecosystem in Indonesia. This study recommends strengthening government policies, fostering collaboration among Islamic financial institutions, and educating the public to support a gradual and integrated dedollarization process.